Analisis Penggunaan E-Learning Madrasah Sebagai Media Pembelajaran Bahasa Arab Di MTsN 2 Kota Surabaya di Era Pandemi Covid-19 - Hamdatul Musyarrofah; Hilma Nailis Syarifiyah; Muhammad Anis Bachtiar (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2021)
The implementation of 4C (Critical Thinking, Communication, Collaboration, Creativity) in the learning process is vital in order to prepare students for the 21st century (Supriano, 2019). In this era which the learning process conducts online, the teachers may still emphasize those values through kinds of questions served especially through e-learning madrasah. Thus, the objectives of this study are to be a reference for the other teachers by exploring the kinds of questions in learning Arabic, also give suggestions or even convey to certain parts so that a revision of e-learning madrasah will be conducted by analyzing the obstacles. Applying descriptive qualitative method, the researchers assume that through the futures of e-learning madrasah the teachers provide PPT/PDF, multiple choices, short answer and essay questions for maharah qiro’ah (reading skill), listening to a video/audio for maharah istima’ wa kalam (listening and speaking skills), fill-in-the-blank, short answer questions as well as asking students to create a simple essay for maharah kitabah (writing skill). Nevertheless, the Arabic font in e-learning madrasah and the learning schedule which is not specific and fixed become the obstacles.